How does the turnover intention of village clinic doctors change after China's new health care system reform? A comparison based on three surveys in a province in eastern China - Lv, Haiyuan; Zhou, Lifang; Yu, Zhaofeng; Shao, Jiaxian; Yu, Yuncong; Yin, Wenqiang; Chen, Zhongming (Frontiers in Public Health, 2023)
Objectives This study aims to analyze the changes in village clinic doctors' turnover intention following the new health care system reform (NHCSR). Methods All the data were obtained from three surveys conducted in 2012, 2015, and 2018 in a province in eastern China. Descriptive analysis and analysis of variance (ANOVA) were used to analyze the changes in village clinic doctors' turnover intention. Results The mean scores of village clinic doctors' turnover intention were 2.87 ± 1.07, 2.76 ± 1.12, and 2.99 ± 1.14 in 2012, 2015, and 2018, respectively, with a significant difference (F = 3.60, P = 0.03). During the 3 years, the turnover intention scores of village clinic doctors who were male, aged 40 years and below, secondary technical school graduates, had the qualifications to practice as village clinic doctors, and were under village-township integrated management first decreased and then increased. The turnover intention scores of village clinic doctors with medical practitioner qualifications increased; however, the scores, decreased for those without village-township integrated management. Conclusion The turnover intention of village clinic doctors has increased, and the possible reasons for this phenomenon include changes in the demographic characteristics of village clinic doctors and policy factors. The government should pay more attention to the problems that village clinic doctors consider of urgent concern, such as the treatment of income and pension insurance, and provide greater career development and training opportunities for village clinic doctors to maintain their motivation and stability.